Monitoring system for the population status of rare and endangered fauna species in ukrainian nature reserves - Mashevska, Marta; Trushevych, Maksym; Holovatyi, Yaroslav (Видавництво Львівської політехніки, 2025)
The article describes the process and results of developing a model for assessing the risk and causes of extinction of rare fauna species in the reserves of the western part of Ukraine, considering specific environmental conditions of the region. An information model of the system has been developed, which includes the collection of data from GPS devices and mapping resources to create an interactive map with population indicators. The process of assessing the status of populations based on fuzzy logic is also described, which allows to take into account uncertainty in the input data and make more accurate predictions about the status of species. The system was implemented using modern technologies such as React for the frontend, Node.js for the backend, Mapbox for interactive maps, andMongoDB for data storage.
Keywords: monitoring; fuzzy model; biodiversity; environmental management; system design